2022-RA-595-ESGO Ovarian stem cells from cryopreserved ovarian cortex: a potential for neo-oogenesis in women with cancer-treatment related infertility. (20th October 2022) - Silvestris, Erica; Minoia, Carla; Cazzolla, Ambrogio; Kardhashi, Anila; de Palma, Giuseppe; Arezzo, Francesca; Loizzi, Vera; de Palo, Raffaella; Dellino, Miriam; Cormio, Gennaro
Abstract : Introduction/Background: Cancer treatment related-infertility (CTRI) affects more than one third of young women undergoing anti-cancer protocols, inducing a premature exhaustion of ovarian reserve. In addition to ovarian suppression by GnRHa, oocyte and cortex cryopreservation has gained great interest although the cortex reimplantation implies a few drawbacks as the risk to reintroduce malignant cells. The capability of ovarian stem cells (OCSs) from fresh ovarian cortex fragments to differentiate in vitro to mature oocytes provides a tool to overcome these drawbacks. In fact, since ovarian cortex sampling and cryopreservation is practicable before gonadotoxic treatments, the recruitment of OSCs from defrosted fragments could provide a novel opportunity to verify their suitability to be expanded in vitro as oocyte-like cells (OLCs). Methodology: A cortex piece from a 28 yrs-woman, submitted to annexiectomy for a benign ovarian cyst, was cryostored in liquid nitrogen for one year. The strips were thawed and the OSCs isolation performed by enzyme-free method. The recruited cell suspension was stratified on Ficoll gradient and centrifuged, then recovered, incubated at 4°C with rabbit polyclonal anti-Ddx4 and followed by further incubation with anti-rabbit-IgG-FITC antibody. The OSC suspension was then incubated with 7-amino-actinomycin-D-labelled with phycoerythrin-5 as viability dye, and evaluated by flow cytometric analyses. Results: The cell population included large consistency of positive cells (A) which were analyzed in their vitality using the PC5-conjugated-7-AAD viability marker. Almost the full population, namely 95.7% of Ddx4 + cells were found viable among a minority equal to 4.3% of dead cells (B-C), suggesting that the fragments cryopreservation in liquid nitrogen is almost indolent on the OSC viability. Conclusion: The consistency of OSC population from a single cryopreserved ovarian cortex after thawing suggest that this population is apparently resistant to the temperature stress for freezing and thawing, thus reinforcing interest for stemness studies in treatment of female CTRI.